Reinforcement of natural rubber latex films by Banana flour. - Azahari, Baharin (Universiti Sains Malaysia, 2012)
Banana stem was processed into powder of particle size of 25 /lm and soaked in 2% sodium hypochlorite at 40°C for various soaking times. Then it was converted to 10% dispersions by ball milling at room temperature at various milling times. The resulting dispersions were added to prevulcanized natural rubber latex (PNRL) compound as filler. Ball milling produced fibre whiskers around the banana stem powder particles which resulted in the increase of toluene uptake of the films. Films containing banana stem powder have lower modulus and tensile strength but higher tear strength. Banana stem powder soaked and ball milled for 24 hours produced films of higher mechanical properties compared to banana stem powder produced with different soaking and milling conditions. PNRL films containing 5 phr of banana stem seemed to have better properties over the other banana filled films, but comparable properties with those films containing inorganic fillers (calcium carbonate and colloidal silica) and the commercial latex glove. The rate of biodegradation of the PNRL films increased with banana stem powder loading and banana stem powder filled PNRL films biodegraded faster than those films containing the same amount of inorganic fillers and the commercial glove.